Variations in the mouth parts of some Hymenoptera - Nixon, Ivan L. (My University, 1903)
Introduction: The group of the order Hymenoptera considered in the present paper is known as the Anthophila ,a name signifying lover of flowers and indicative of their food habits. In order that they may procure their food they have mouth parts peculiarly adapted to the gathering of honey. This group is also characterized by having the basal joint of the posterior tarsi dilated into an oblong or sub-triangular plate which is generally hirsute on the inside and provided with instruments for collecting and carrying pollen. In this group the jaws are strong, being varied in different species according to the work done by the particular species; the maxillae and labium are elongated and often transformed into a proboscis capable of being folded up several times beneath the head, the labium being pilose at the extremity. This group Anthophila is divided into two families, Andrenidae and Apidae; the first family may be defined as the short tongued bees and the second as the long tongued bees. In the Andrenidae the mentum is elongated and the labium at its extremity small and either spear shaped or cordate; with a small ear shaped lobe on each side, and being either straight or very slightly denexed in some and reflexed in others; the labium and terminal maxillary lobes not forming an elongated proboscis. The palpi are jointed, the joints being cylindrical and longer than wide; the labial palpi are four jointed and are similar to the maxillary palpi which are six jointed. The mandibles are simple or terminated by one or two notches. The insects composing the family Apidae have the mentum long, with the abium at its extremity forming an elonuted, slender seta, reflexed when at rest, and as long or longer than the mentum, with two small ; lateral filaments, and forming with the maxillae, an elongated proboscis, capable of being porrected in front of the head when in action, or folded up beneath the head and breast when at rest, in the shape of a flattened . The palpi, atteched at the base of the labium, form two slender flattened filaments often as long as the labium itself, the two basal joints being very long, with the two apical joints minute, and obliquely affixed near the extremity of the second joint; the maxillary palpi vary in the number of joints from one to six.
Citation: Nixon, Ivan L. Variations in the mouth parts of some Hymenoptera. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Entomology; Bees; Anthophila; Hymenoptera; Anatomy; Mouth Parts; Theses